PASANG RI KAJANG - Hijjang, Pawennari; Jafar N, Muh. Kamil; Sanduan, Varis Vadly; Amiluddin, Amiluddin; Wulandari, Sindi (International Conference on Cultural Studies, 2019)
This paper to analyze the village of forest in Tana Toa, the locality of South Sulawesi that   is   headed   by   the   Ammatowa .   The   Keammatoan ,   the   term describing the society whose members live in the area of Tana Toa, is divided into the Ilalang embaya , who have maintained their exclusiveness and sharp borders, and the Ipantarang embaya , who have mixed with other members of the surrounding society. Among the Ilalang embaya there is a set of adat regulations based on Pasang that demands obedience to is detailed. Prescriptions in such contexts as shape, zise , and orientation of housing that must be built. The force of adat allows possibilities of empowering local institutions for managing forest resources in the context of  the future scenario of regional autonomy. This paper considers the question of the extent to which the institution of Ammatoa leadership and is associates adat constitute an institution that has fully been used for the village forest in this locality of South Sulawesi. It especially considers the question of how these institutions can be updated   and contextualized  though  a  process  of  reflective  mutual understanding to cope with the context of regional autonomy. The papar concludes by investigating the reality of changes in the Ammatoa system as it responds not only to the expansion of the forest resource management requirements, but also the imperatives to transform into an open community.